The Effectiveness of Duolingo Apllication to Increase Student’s Listening Skills, a Case of The Fifth Gradestudent’s of SD Negeri Langgenharjo 01 Juwana - Evelyn Atalya, Rara; Himatu Karima, RR. Festi; Hidayat, Nur (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study examines the impact of the Duolingo app on enhancing the listening skills of fifth-grade students at SD Negeri Langgenharjo 01 Juwana. Using a quasi-experimental design, this research involved 23 students categorized into a treatment group and a comparison group. The experimental group used Duolingo for listening exerciseswhereas the control group utilized traditional listening approaches. Data was gathered through initial and final assessments, followed by statistical analysis using the t-test and N-gain test. Findings demonstrated a notable enhancement in the listening abilities of the experimental group relative to the control group. The mean pre-test score for the experimental group stood at 61.25, which rose to 80.83 in the post-test. In contrast, the control group's average score increased slightly from 56.45 to 58.81. The t-test results indicated a statistically significant difference (p < 0.05), confirming that Duolingo effectively enhances students' listening skills. These findings support the use of technology-based learning tools in language education, particularly for listening comprehension. Duolingo's interactive and gamified approach increases student engagement and motivation, making it a valuable supplement to traditional learning methods. This study suggests that integrating Duolingo into the curriculum can enhance students' listening skills and overall language proficiency.